1982
DOI: 10.1073/pnas.79.20.6294
|View full text |Cite
|
Sign up to set email alerts
|

Thyrotropin-releasing hormone mobilizes Ca2+ from endoplasmic reticulum and mitochondria of GH3 pituitary cells: characterization of cellular Ca2+ pools by a method based on digitonin permeabilization.

Abstract: Treatment of 45Ca24-loaded GH3 pituitary cells with various concentrations of digitonin revealed discrete pools (I and II) of cellular 45Ca2+ defined by differing detergent sensitivities. Markers for cytosol and intracellular organelles indicated that the two 45Ca2+ pools were correlated with the two major cellular Ca2+-sequestering organelles, endoplasmic reticulum (I) and mitochondria (II). Studies with various inhibitors were consistent with these assignments. Mitochondrial uncouplers preferentially deplete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
21
0

Year Published

1983
1983
1992
1992

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(26 citation statements)
references
References 24 publications
(15 reference statements)
5
21
0
Order By: Relevance
“…In summary, nimodipine will have little effect on stimulus-secretion coupling in healthy anterior pituitary cells for three reasons: (1) nimodipine is a very weak inhibitor of Ca entry through the transient Ca channels; (2) high-affinity block of the slowly inactivating Ca channels does not occur to a significant extent under physiological conditions; (3) nimodipine does not inhibit the intracellular release of Ca (as evidenced by the lack of effect on TRH-induced secretion, which involves release of cell Ca in response to an increase of inositol triphosphate (Ronning, Heatley & Martin, 1982;Gershengorn, Geras, Spina, Purello & Rebeechi, 1984)). …”
Section: Discussionmentioning
confidence: 99%
“…In summary, nimodipine will have little effect on stimulus-secretion coupling in healthy anterior pituitary cells for three reasons: (1) nimodipine is a very weak inhibitor of Ca entry through the transient Ca channels; (2) high-affinity block of the slowly inactivating Ca channels does not occur to a significant extent under physiological conditions; (3) nimodipine does not inhibit the intracellular release of Ca (as evidenced by the lack of effect on TRH-induced secretion, which involves release of cell Ca in response to an increase of inositol triphosphate (Ronning, Heatley & Martin, 1982;Gershengorn, Geras, Spina, Purello & Rebeechi, 1984)). …”
Section: Discussionmentioning
confidence: 99%
“…In a study on other tissues, Elias, Goerke, Friend & Brown (1978) showed that digitonin selectively permeabilizes cell membranes and that this is likely to be due to their different cholesterol content compared to intracellular organelles (plasma membrane > endoplasmic reticulum > mitochondria). Beside other uses, digitonin has been utilized to analyse the mechanism of secretion in different types of cells (Ronning, Heatley & Martin, 1982;Dunn & Holz, 1983;Wilson & Kirschner, 1983).…”
Section: Discussionmentioning
confidence: 99%
“…Rubin 1982). In PRL cells including those of teleost fish, Ca + + influx may be derived from action potentials which involve a Ca + + component and whose frequency can be increased or decreased by stimulators or inhibitors of PRL release (Taraskevich and Douglas 1978;Ronning et al 1982).…”
Section: The Role Of Ca + + In Stimulus-secretion Couplingmentioning
confidence: 99%